Early-life famine exposure may modify the association between long-term temperature variability and cardio-cerebrovascular diseases: a nationwide study - Yao Wu; BinBin Su; Junqing Xie; Bo Wen; Xiaolan Wu; Mengfan Wang; Yanhui Dong; Yi Song; Jun Ma (Environmental Research: Health)
We aimed to evaluate whether the association between long-term temperature variability (TV) and cardio-cerebrovascular diseases (CCVDs) was affected by famine exposure in different age stages. We used data from the fourth national urban and rural elderly population survey (2015). Participants were categorized into six groups based on their age at famine exposure (famine exposure under age 5, between ages 5 and 18, and during adulthood) and the severity (severely affected areas versus mildly affected areas) of the Great Chinese Famine (1959–1961) in their province of residence. Mixed-effects logistic regression model was used to quantify the association between long-term TV and the prevalence of CCVDs across six famine-exposed groups. A total of 222 179 participants were included. In severely affected areas, the odds ratio (OR) of CCVDs associated with per 1 °C increase in 5 year average TV were 1.07 (95% confidence interval [CI]: 1.02, 1.13) for those exposed to famine during adulthood, 1.28 (95% CI: 1.17, 1.40) under the age of 5 years. Urban residence, higher education, increased household income, and more frequent physical activity could mitigate the association between TV and CCVDs, particularly among those exposed to severe famine before the age of 5. Individuals exposed to famine before the age of 5 are more susceptible to TV-related CCVDs compared to those exposed during adulthood. Our findings highlight the importance of early-life nutrition in lowering susceptibility to CCVDs later in life.